BUDIDAYA IKAN LELE DI DESA SEMERAP SEBAGAI UPAYA PEMULIHAN EKONOMI PADA MASA PANDEMI COVID-19 - Syarif, Dafiar; Wahyu, Wawan Devis; Nilda, Elvi; Melani, Zahaqi; Natasya, Widia (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Covid-19 pandemic has affected the growth of MSMEs in Semerap village. This study aims to describe the problems faced by catfish farmers in Semerap village. Data collection methods are observation and interviews. The resource person for this study is a catfish farmer. Interview results show that poor water quality affects catfish production. Low prices for catfish and expensive feed are also other problems faced by farmers.